Ivy + Bean doomed to dance - Barrows, Annie; Blackall, Sophie (San Francisco : Chronicle Books, 2009)
Second-grade best friends Ivy and Bean beg for ballet lessons, then, when they are cast as squids in their first recital, scheme to find a way out of what seems to be boring, hard, and potentially embarrassing.
KVBA Nominee 2010-11
Keywords: Ballet -- Fiction; Best friends -- Fiction; Friendship -- Fiction